Inhibitory Effect of Two Traditional Chinese Medicine Monomers, Berberine and Matrine, on the Quorum Sensing System of Antimicrobial-Resistant Escherichia coli - Sun, Tong; Li, Xiao-Dong; Hong, Juan; Liu, Can; Zhang, Xin-Luo; Zheng, Jin-Ping; Xu, Yuan-Jun; Ou, Zheng-Yang; Zheng, Jing-Ling; Yu, Dao-Jin (Frontiers in Microbiology, 2019)
The quorum sensing (QS) system controls bacterial biofilm formation, which is highly related to the virulence and resistance of pathogens. In the present study, the effect of two traditional Chinese medicine (TCM) monomers, berberine and matrine, on biofilm formation and QS-related gene expression of antimicrobial-resistant (AMR) Escherichia coli strains was investigated by laser scanning confocal microscopy (LSCM) observation and real-time PCR. The results indicated a roughly positive relationship between biofilm formation ability and antimicrobial resistance. LSCM observation showed that berberine and matrine inhibited biofilm formation of AMR E. coli strains at 1/2 minimal inhibitory concentration (MIC) (1/2 MIC berberine at OD630: 0.1020; 1/2 MIC matrine: OD630: 0.1045); furthermore, abnormal cell morphology such as rounded and elongated cells was also observed. This finding was consistent with the downregulation of QS-related genes: luxS, pfS, sdiA, hflX, motA, and fliA. At 1/2 MIC and 1/4 MIC concentrations of berberine, a significant downregulation of luxS, pfS hflX, ftsQ, and ftsE was observed. The results indicate that berberine and matrine can inhibit biofilm formation by inhibiting the QS system and that berberine is more effective than matrine.